Inovasi perpaduan clutch bag dan obi “Clobi” sebagai aksesori mode multifungsi - Nurwahyuni, Linda; Widihastuti, Widihastuti (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2025)
The creation of this product innovation work aims to analyze the production process of making “Clobi” products and the level of public preference for “Clobi” products. This product innovation method is RnD with the 4D model, namely definition, design, develop, and disseminate. The result of this product innovation is the production process of making “Clobi” products made using the main material of satin fabric and additional sequins made in such a way that it functions as a clutch bag and obi. 2) The level of public liking for the “Clobi” product based on the favorability test conducted on the “Clobi” product on the design indicator, shows that the shape of the design is 73.3% very favorable and the placement of the motif is 66.6% very favorable. In the aesthetic indicator, the results of the favorability test show that the aesthetics of the clutch bag 83.3% are highly favored and the aesthetics of the obi 80% are highly favored. On the function indicator, the favorability test results show that the clutch bag function is 60% highly preferred and the obi function is 83.3% highly preferred. Meanwhile, on the total look indicator, the results of the favorability test showed that 70% were highly favored. This shows that “Clobi” products can be well received by the public. By seeing the good response from the community, it is hoped that “Clobi” products can be mass produced and then marketed. Future researchers can further develop the materials used and other designs according to the target market.